CULTURAL AND CREATIVE TOURISM: THE CASE OF ‘CELEBRATIONS’ IN THE ALGARVE REGION - Maria Manuela Guerreiro; Cláudia Henriques; Júlio Mendes (Journal of Spatial and Organizational Dynamics, 2019)
This study sought to investigate the importance of cultural and creative tourism associated with ‘celebrations’ (i.e., festivais, festas, feiras and eventos [festivals, feasts, fairs and events]) in the Algarve region of Portugal. The resulting paper first discusses the significance of cultural and creative tourism and its interconnections with sustainable development in a region traditionally linked with ‘sun and sea’ tourism products. The methodological framework was a case study that focused on links between cultural and creative tourism and the dynamics of celebrations in 16 Algarve municipalities (concelhos municipais). The study was based on content analysis of data gathered with a questionnaire distributed to camara municipal (city council) culture and/or tourism responsibles from the 16 Algarve municipalities, namely, those (technicians) whose jobs are related to enhancing the attractiveness of the cultural resources associated with celebrations. The results reveal an increasing recognition of the importance of cultural patterns to municipals’ tourism offers based on popular and everyday culture, which contribute to the Algarve’s authentic identity and heterogeneous features.